Karnal bunt A threat to export of Indian wheat - Bala, Ritu; Kaur, Jaspal (Indian Farming, 2021)
Karnal bunt (KB) is a disease of quarantine, thus affects the wheat export. The disease is prevalent in North western states of India which contributes the maximum share to the national pool. At present, none of the recommended variety is resistant to Karnal bunt in these states. Thus, there is a dire need to manage the disease. Further, the disease is highly dependent on environmental factors and it is difficult to predict. Thus, an attempt was made to study the effects of factors responsible for KB high years. The data showed a clear cut role of inoculum build up along with prevalent weather and presence of susceptible cultivars in all the KB high years. The data analyzed can be helpful in managing the KB at various levels to make the country disease free.